Design and Development of a Secure Data Encryption and Decryption System - Shepherd Mwaekwa Wamulume, (Indian Journal of Cryptography and Network Security (IJCNS), 2025)
In an increasingly interconnected world, the need to secure sensitive information has become paramount. This article presents the Design and development of a secure data storage system. An encryption and decryption system aimed at enhancing the confidentiality, integrity, and availability of digital data. The proposed system employs advanced cryptographic algorithms to provide robust protection against unauthorised access, data breaches, and cyberattacks. The design phase emphasises the integration of both symmetric and asymmetric encryption techniques, enabling the system to cater to a diverse range of applications, from secure file storage to encrypted communications. Key Management protocols are implemented to ensure the safe generation, distribution, and storage of encryption keys, a critical component of secure systems. The system was developed using modern programming tools and frameworks, adhering to industry standards such as AES (Advanced Encryption Standard) and RSA (Rivest-Shamir-Adleman). Extensive testing was conducted to evaluate the system’s performance, security resilience, and scalability. Results demonstrate the system’s ability to resist common attacks, including brute force and cryptanalysis, while maintaining high efficiency in data processing. This research contributes to the field of data security by providing a versatile and secure solution that can be adapted for use in industries such as finance, healthcare, and e-commerce. Future work includes integrating post-quantum cryptographic algorithms to prepare for the advent of quantum computing.